Pengaruh Metode Pembelajaran Renang Terhadap Kondisi Fisik Siswa Anak Usia 10 Tahun Di Sdn 016 Tanah Merah - Rezki, Rezki; Dupri, Dupri; Islami, Vebi; Anastasia, Elva (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
Learning is a process of interaction between students and educators and learning resources in a learning environment. Therefore, the role of the principal as an intermediary connecting the education system, teachers and performance must be perfected. Research objectives: (1) to investigate further about the level of job satisfaction of physical education teachers and (2) to see the effect of the swimming learning method on the physical condition of students in 10-year-old children at SDN 016 Tanah Merah. Research Method: The approach in this study uses the